Stem Cell Mobilization Is Lifesaving in a Large Animal Preclinical Model of Acute Liver Failure. Issue 4 (October 2018) - Ahmadi, Ali R.; Chicco, Maria; Wesson, Russell N.; Anders, Robert A.; Dor, Frank J. M. F.; IJzermans, Jan N. M.; Creamer, Tyler J.; Williams, George M.; Sun, Zhaoli; Cameron, Andrew M.
Abstract : Introduction: Acute liver failure (ALF) affects 2000 Americans each year with no treatment options other than liver transplantation. We showed previously that mobilization of endogenous stem cells is protective against ALF in rodents. The objective of this study was to assess whether stem cell mobilizing drugs are lifesaving in a large animal preclinical model of ALF, to assess readiness for a clinical trial. Methods: Male Yorkshire pigs (14–18 kg) were divided into 2 groups, control (n = 6) and treatment (n = 6). All pigs received an intravenous bolus of the hepatotoxin D-galactosamine (0.5 g/kg) via central line and were followed up until death or day 28. Treated animals received simultaneous intramuscular injection of plerixafor (1 mg/kg) and G-CSF (2 μg/kg) at baseline, 24 and 48 hours after toxin infusion to mobilize endogenous stem cells, as previously described. Control animals received saline. Results: All control animals (6/6) succumbed to liver failure within 91 hours, confirmed by clinical, biochemical, and histopathological evidence of ALF. In the treatment group (5/6) animals survived indefinitely despite comparable biochemical changes during the first 48 hours ( P = 0.003). White blood cell count increased by a mean of 4× in the treated group at the peak of mobilization ( P = 0.0004). Conclusions: Stem cell mobilizing drugs were lifesaving in a preclinical large animal model of ALF. Since no therapeutic options other than liver transplantation are currently available for critically ill patients with ALF, a multicenter clinical trial is warranted. Abstract : Supplemental Digital Content is available in the text